Supervisi Akademik Kepala Sekolah Taman Kanak-kanak Dimasa Pandemi Covid 19 - Jhoni Warmansyah (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The Covid 19 pandemic has an impact on the difficulty of school principals in carrying out academic supervision in their institutions in order to ensure the continuity of the quality of education in Kindergarten institutions. The purpose of this study is to determine the implementation of academic supervision of kindergarten school principals in the midst of the Covid 19 pandemic. This study used a qualitative method with explorative case studies. The study was conducted at the Samba Taruma Kindergarten in Bekasi Regency in 2019/2020. Sampling uses purposive sampling. Respondents used as research samples are the principal and 3 teachers. Data collection uses semi-structured interviews by making a list of questions. Data analysis uses thematic data analysis. The results showed the implementation of academic supervision amid the Covid 19 pandemic by the Head of the Samba Taruma Kindergarten was going well. This can be seen from the supervision process in the form of online daily discussions, assisting teachers to overcome problems, inventory the basic competency achievements, and provide feedback on evaluating the successful learning process.